Figurative Language in the Lyrics of Songs on Adele’s “21” Album - Ridhaswari Isnainingrum Fatihah; Rr. Astri Indriana Octavita; Agung Prasetyo (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
This study aims to find out what figurative language is contained in the song lyrics on Adele's